2020
DOI: 10.21098/jimf.v6i2.1159
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Financial Development, Economic Growth and Co2 Emission in Indonesia

Abstract: This study aims to investigate the dynamic relationship between Islamic financial development, economic growth, and CO2 emissions with Environmental Kuznets Curve (EKC) approach in Indonesia over the 2000-2018 period.  This study employs the Auto Regressive Distributed Lag (ARDL) bound testing approach and the Error Correction Mechanism (ECM) to examine the existence of long-run and short-run relationship between variables. From the results of the model, we do not find any support for the existence of the EKC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Islamic social finance can also be said to play an essential role in the social safety net program for the affected community (Malik & Senjiati, 2020) while increasing knowledge literacy about types of Islamic social, financial instruments such as zakat, infaq, shadaqah, and waqf (ziswaf) so that the public more knows them in addition to Islamic commercial financial literacy which is currently still being promoted (Iskandar et al, 2020). The form of Islamic social finance contributions can vary greatly depending on the community's needs, such as direct cash assistance (BLT), assistance for material needs such as necessities, health service assistance, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Islamic social finance can also be said to play an essential role in the social safety net program for the affected community (Malik & Senjiati, 2020) while increasing knowledge literacy about types of Islamic social, financial instruments such as zakat, infaq, shadaqah, and waqf (ziswaf) so that the public more knows them in addition to Islamic commercial financial literacy which is currently still being promoted (Iskandar et al, 2020). The form of Islamic social finance contributions can vary greatly depending on the community's needs, such as direct cash assistance (BLT), assistance for material needs such as necessities, health service assistance, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, all Islamic economic instruments have the potential to become a means of increasing aggregate demand and aggregate supply to the right so that the economic surplus is re-established and helps accelerate economic recovery (Iskandar et al, 2020) by alleviating the crisis faced by the middle to low-income groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the Islamic finance framework, published works on this topic are very limited. Among them are Iskandar et al (2020) who studied the dynamic relationship between CO 2 emissions, Islamic financial development, and economic growth in Indonesia using the Environmental Kuznets Curve (EKC) approach. The findings showed no significant short-term dynamic relationships between growth, development of Islamic finance, and CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study's findings also revealed that all the variables are positively related to manufacturing sector production. Iskandar et al, (2020) determined the nature of development economics in Indonesia. Important aspects, such as variables that influence economic development in a city as a result of government allocation, are also considered.…”
Section: Literature Reviewmentioning
confidence: 99%